Factor analysis of teacher job satisfaction before and during WFH: Evidence from Indonesia - Setiorini, Amanda; Rachmarwi, Wiwik; Nurfadillah, Dety (Edelweiss Applied Science and Technology, 2025)
This research aims to conduct a factor analysis of nine factors that influence teacher job satisfaction before and during Work from Home (WFH). This research employed a quantitative approach to investigate job satisfaction before and during WFH. Data collection involved surveys consisting of nine variables distributed to school teachers through instant messaging and got 97 respondents. The collected data was then analyzed using factor analysis from SPSS which helped to identify factors that explain the relationship between variables. Several factors remain dominant: the most dominant factors are Working Conditions, Income, Work Itself; the Colleagues factor remains in second dominance; and the Recognition factor remains in third dominance. However, the Responsibility, Advancement, and Supervision factors experienced a significant decrease in dominance, while the Security factor showed a significant increase in dominance. WFH itself is a change that needs to be managed well, apart from infrastructure, but also psychological readiness. And, because job satisfaction is a positive emotional state that results from a person’s appreciation of their work or their own experiences, the psychological factors need attention. It was found that psychological readiness has not received much attention compared to others, for example, online infrastructure.